Time for pragmatic, prospective clinical trials to determine the role of empirical antibacterial therapy in critically ill adults hospitalized with malaria. (January 2021) - Hanson, Josh; Nyein, Phyo Pyae; Aung, Ne Myo; Kyi, Mar Mar
Highlights: Children with severe malaria commonly have a concomitant invasive bacterial infection. Empirical antibacterial therapy is therefore recommended in these children. Recent data have challenged the dogma that bacterial co-infection is rare in adults. It is difficult to confidently exclude bacterial co-infection in adults with malaria. Empirical antibiotics should also be considered in critically ill adults with malaria. Abstract: Background: Children with severe falciparum malaria in malaria-endemic regions are predisposed to developing life-threatening bacterial co-infection. International guidelines therefore recommend empirical broad-spectrum antibacterial therapy in these children. Few studies have examined co-infection in adults, although it has been believed to be relatively rare; antibacterial therapy is therefore not routinely recommended in adults with falciparum malaria. Discussion: However, the fundamental pathophysiology of falciparum malaria in adults and children is the same; it is therefore unclear why adults would not also be predisposed to bacterial infection. Indeed, recent studies have identified bacteraemia in >10% of adults hospitalized with malaria. Some have suggested that these adults probably had bacterial sepsis, with the parasitaemia an incidental finding. However, it is usually impossible in resource-limited settings to determine–at presentation–whether critically ill, parasitaemic adults have severe malaria, bacterial sepsis, or both. Given the significant case-fatality rates of severe malaria and bacterial sepsis, the pragmatic initial approach would be to cover both possibilities. Conclusions: Life-threatening bacterial co-infection may be more common in critically ill adults with malaria than previously believed. While further prospective data are awaited to confirm these findings, it might be more appropriate to provide empirical aantibacterial cover in these patients than current guidelines suggest.